Faience Tiles with Biblical Subjects in the Interiors of the Menshikov Palace in St. Petersburg: Origins, Sources, Analogies - Andreeva, Ekaterina A. (Actual Problems of Theory and History of Art, 2018)
There was a new finishing material, Dutch painted faience tiles, which appeared during the reign of Peter I in Russia. It was used in the interiors of royal palaces and palaces of the nobility as decorative tiles. Nowadays the genuine “tile” interiors preserved in St. Petersburg in the Summer Palace of Peter the Great and in the Aleksander Menshikov palace. Tiles with biblical subjects were found in both palaces. However, in the Summer Palace, these tiles appeared only during the restoration of 1957. The tiles in the Menshikov Palace are authentic. The tiles, 13 by 13 cm in size, contain a whole plot, or rather a line, sometimes, a few lines from the Bible depicted on them. L. P. Dorofeeva and R. V. Rebrova have conducted a study on the tiles with biblical subjects from the Menshikov palace. These tiles have never been attributed before. The plots were not defined (or not accurately determined), no comparison with the sources was made, and no analogues have ever been found.The article reveals the plots depicted on the tiles. It is possible in some cases to establish which lines and from which Gospels are depicted. As a result of the research of the production, the quality of painting and other features, the tiles on biblical subjects were divided into three groups. Ten tiles were made in Amsterdam on engravings by P. Schut; one for an unknown engraving in Amsterdam or Rotterdam. The tiles of the third group were made in Utrecht; they have their own stylistic features and are made not by engraving.
Keywords: Menshikov Palace; Dutch tiles; Gospel; Facial Bible of Piscator; Pieter Hendrickszoon Schut